REHABILITATION THERAPY AFTER TOTAL HIP ARTHROPLASTY - Mihai Constantinescu (Editura Univeristatii "Stefan cel Mare" din Suceava, 2021)
The purpose of our study is to present some general aspects regarding approach to the therapeutic path in the case of the hip prosthesis following a trauma to the lower limb and femoral neck fracture in the elderly. This surgery seems quite easy nowadays, when the surgical techniques are a real progress in terms of means of investigation and treatment. However, the approach must be taken on a case-bycase basis. To understand the pathophysiological mechanisms and the application of the therapeutic means in hip prosthesis, we will present a case study in which we will apply specific kinetic means to post-surgical recovery.